Species composition and distribution of seaweeds in Phu Yen province - Hang, Nguyen Thi Thu; Tu, Nguyen Van; Phu, Vo Van; Lam, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2021)
Results of four field surveys, conducted from June 2017 to June 2018 found that in the Phu Yen coastal water, a total of 103 seaweed species have been recorded, increasing the total number of seaweed species in Phu Yen province to 133 species, with 81 newly recorded species for Phu Yen geographic area. Among 103 seaweed species, 4 species belong to Cyanobacteria, 38 species belong to Rhdophytes, 24 species belong to Phaeophytes, and 37 species belong to Chlorophytes.  The number of species at surveyed sites V1 to V9 varies from 3 species/site (V3) to 83 species/site (V7) and on average 27 species/site. Sørensen’s similarity coefficient varies from 0.05 (between V3 and V7) to 0.86 (V3 and V4) and on average 0.25. 74/103 species were collected in the littoral zone, 67 species in sublittoral zone and most of them are distributed at 0-4 m water depth of subtidal zone. The marine algal flora is represented by mixing of subtropical and tropical characteristics as Cheney index was 3.